Fourth Five-Year Plan Madras State Preliminary Memorandum - Planning Commission (Planning Commission, 1965)
The basic decisions governing the rate of growth, the size and pattern of investment arc all taken at the National level. the State Plan should conform broadly to the targets and objectives of the National Plan and assist in their fulfilment ; it should also be consistent with the Economic and Social Philosophy underlying the National Plan. But within this framework, deviations from the All-1 ndia pattern with reference to local problems and local needs arc inevitable.
Finance (Planning) Department Government of Madras